1977
DOI: 10.1111/j.1600-0722.1977.tb00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental palatal candidosis and saliva flow in monkeys

Abstract: – Maxillary acrylic plates, inoculated with Candida albicans, were inserted for 3 weeks in 10 monkeys (Cercopithecus aethiops) (Series I), and reinserted in five of the animals 8 weeks after removal (Series II). To suppress saliva flow oxyphencyclimine was injected intramuscularly (0.125 mg/kg) thrice daily for 3 weeks in six monkeys of Series I, while four controls received no drug. In Series II the oxyphencyclimine dose was doubled in three animals, and two controls were sham‐treated with sodium chloride. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…The attachment of certain oral bacteria to hydroxyapatite is similarly inhibited by saliva (Clark and Gibbons, 1977;Gibbons and van Houte, 1980). Our results also support the in-situ observations of Olsen and Haanaes (1977) that yeast colonisation of acrylic plates worn by monkeys with a reduced salivary flow was increased. Furthermore, chronic oral candidal infections are commonly seen in patients with Sjogrens syndrome, whose salivary flow is absent or minimal (MacFarlane and Mason, 1974).…”
Section: Discussionsupporting
confidence: 85%
“…The attachment of certain oral bacteria to hydroxyapatite is similarly inhibited by saliva (Clark and Gibbons, 1977;Gibbons and van Houte, 1980). Our results also support the in-situ observations of Olsen and Haanaes (1977) that yeast colonisation of acrylic plates worn by monkeys with a reduced salivary flow was increased. Furthermore, chronic oral candidal infections are commonly seen in patients with Sjogrens syndrome, whose salivary flow is absent or minimal (MacFarlane and Mason, 1974).…”
Section: Discussionsupporting
confidence: 85%
“…Other predisposing factors for oral candidiasis that have come under scrutiny in a number of animal models include broad-spectrum antibiotic therapy (5,82,(155)(156)(157), carbohydrate-rich diets (66,154,155), topical use of corticosteroids (47), corticosteroid inhalation (28), trauma (131), iron deficiency (147,185), diabetes (51), xerostomia (1,83,84,119,133), decrease in CD4 ϩ T-cell counts and phagocytic function (31,32), defective T-cell function (16), and immunosuppressive therapy (27,172). Undoubtedly, these studies have helped us to understand the etiology of oral candidiasis and the development of the management protocols that are currently prevalent.…”
Section: Need For and Clinical Relevance Of Animal Modelsmentioning
confidence: 99%
“…However, primates are relatively expensive and difficult to maintain, especially for large-scale experiments. Some workers have also reported that artificial oral infestation of monkeys with Candida is difficult and unreliable (133). Hence, the monkey model has been largely replaced by smaller mammals such as rats and mice, which have gained popularity.…”
Section: Pros and Cons Of Current Animal Models Monkey Model (Macaca mentioning
confidence: 99%
See 1 more Smart Citation
“…Also used were macaques (Budtz-Jorgensen, 1971, 1973Olsen & Haanaes, 1977) and BI0 87.20 hamsters (McMillan & Cowell, 1985). All the above experimental animals with the exception of the mice were noninbred.…”
Section: Streptococcus Salivarius and Streptococcus Mitiormentioning
confidence: 99%